Dynamics of Life of People’s Palm Plantation Farmers in Silaut South Coast District (1992-2023) - Afdalia, Firga Ries; Herwandi, Herwandi; Nopriyasman, Nopriyasman (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research discusses the dynamics of the lives of smallholder oil palm farmers in Silaut Pesisir Selatan. Palm oil was first introduced by transmigration residents from the island of Java and has become the main economic sector of the Silaut community today. This palm oil not only provides welfare to palm oil farmers but also to oil palm farm workers. This research uses a socio-economic historical approach using structural functionalism theory. The research method used in this research is a historical research method which is carried out through four stages, namely heuristics, source criticism, interpretation and historiography. The results of this research show the important role of the transmigration community in Silaut in developing oil palm plantations which are then adopted by the surrounding community. Palm oil is the main commodity because the land in Silaut has thick peat and is not suitable for rice farming. Palm oil has become the main economic sector since 2012 and will continue to grow until 2023, so that there are no more rice fields or rice farmers in Silaut. A significant economic increase occurred in 2021-2022 which was caused by the high price of palm oil at that time. Prosperity can be felt by all farmers including workers, so that palm oil changes the life structure of the people in Silaut and has a positive impact on the regional economy and improves existing infrastructure.